USING VOCABULARY DICE GAME IN TEACHING VOCABULARY TO ELEMENTARY SCHOOL STUDENTS - Lukman Nul Hakim; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2018)
This article aimed to describe the use of Vocabulary Dice Game in teaching vocabularyto elementary schoolstudents.Vocabulary Dice Game is versatile game that provides variety of instruction and can be adjusted depend on the needs of the objectives in vocabulary learning.Versatile game means, teacher can adjust what words the students need to learn, and create set of rules or instruction depend on students’ level. The versatility of this game canbenefit the learning process, not only making the students play through learning, but teacher will able to create a strategy in teaching vocabulary that is suitable to students characteristics and development.Vocabulary Dice game as teaching technique in the classroom provides fun and enjoyable learning process. Learning vocabulary is not always about drilling or repeating words but it can be done by act, draw or mime while playing game.By using this game, the learning process is expected to be fun and enjoyable for the students and enhance their memory about the material have been learned as it is obtained through enjoyable way.